2021
DOI: 10.1093/plcell/koab123
|View full text |Cite|
|
Sign up to set email alerts
|

Loss of inner-envelope K+/H+ exchangers impairs plastid rRNA maturation and gene expression

Abstract: The inner-envelope K+ EFFLUX ANTIPORTERS (KEA) 1 and 2 are critical for chloroplast development, ion homeostasis, and photosynthesis. However, the mechanisms by which changes in ion flux across the envelope affect organelle biogenesis remained elusive. Chloroplast development requires intricate coordination between the nuclear genome and the plastome. Many mutants compromised in plastid gene expression (PGE) display a virescent phenotype, i.e. delayed greening. The phenotypic appearance of Arabidopsis thaliana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 94 publications
4
21
0
Order By: Relevance
“…Again, we detected no differences from WT in any of the photosystem-II-related parameters. This indicates that the lack of PEC1 and PEC2 neither impacts photosynthesis nor chloroplast function under normal growth conditions—a striking difference from envelope K + /H + exchanger mutants kea1kea2 ( Kunz et al, 2014 ; deTar et al, 2021 ) but also from Mn 2+ /Ca 2+ carrier deficient cmt1/bicat2 lines ( Eisenhut et al, 2018 ; Zhang et al, 2018 ; Frank et al, 2019 ). Because of the importance of plastid ion carriers and their impact on the leaf ionome, several mutants show aberrations from the WT in ionomics experiments ( Shikanai et al, 2003 ; Eisenhut et al, 2018 ; Zhang et al, 2018 ; Höhner et al, 2019 ).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Again, we detected no differences from WT in any of the photosystem-II-related parameters. This indicates that the lack of PEC1 and PEC2 neither impacts photosynthesis nor chloroplast function under normal growth conditions—a striking difference from envelope K + /H + exchanger mutants kea1kea2 ( Kunz et al, 2014 ; deTar et al, 2021 ) but also from Mn 2+ /Ca 2+ carrier deficient cmt1/bicat2 lines ( Eisenhut et al, 2018 ; Zhang et al, 2018 ; Frank et al, 2019 ). Because of the importance of plastid ion carriers and their impact on the leaf ionome, several mutants show aberrations from the WT in ionomics experiments ( Shikanai et al, 2003 ; Eisenhut et al, 2018 ; Zhang et al, 2018 ; Höhner et al, 2019 ).…”
Section: Resultsmentioning
confidence: 96%
“…Thus far, only two K + /H + exchangers from the K efflux antiporter (KEA) family have been characterized in more detail ( Aranda-Sicilia et al, 2012 ; Kunz et al, 2014 ). Both carriers (KEA1 and KEA2) physiologically function in pH and ion homeostasis which is critical for plastid gene expression and development ( Aranda Sicilia et al, 2021 ; deTar et al, 2021 ). The IE membrane potential of at least −70 mV on the stromal side ( Wu et al, 1991 ) makes K + /H + valves such as KEA1/2 a necessity for osmoregulation to balance K + influx and prevent rupture of plastids ( Bernardi, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our group recently reported that the loss of KEA1 and KEA2, the two inner envelope membrane carriers, affects ion homeostasis, rRNA processing in the stroma, and concomitant plastid gene expression (PGE). As a consequence, the GENOMES UNCOUPLED 1 (GUN1)-dependent retrograde signaling (RS) pathway is activated to halt organelle biogenesis through suppression of GOLDEN2-LIKE (GLK) transcription factors and their targets, photosynthesis-associated nuclear-encoded genes (PhANGs) ( DeTar et al, 2021 ). These insights were enabled by a unique salt rescue phenomenon inherent to the virescent (pale young leaves) of kea1kea2 loss-of-function mutants ( Kunz et al, 2014 ).…”
mentioning
confidence: 99%
“…These insights were enabled by a unique salt rescue phenomenon inherent to the virescent (pale young leaves) of kea1kea2 loss-of-function mutants ( Kunz et al, 2014 ). When mutant plants are treated with moderate concentrations of NaCl, they exhibit a recovery in plastid rRNA metabolism, higher rates of PGE, more wild-type (WT)-like expression of nuclear-encoded genes, and finally greener rosettes with higher chlorophyll (Chl) content and increased photosynthetic rates ( DeTar et al, 2021 ). Here, we endeavor to better understand the mechanism of the salt rescue in kea1kea2 through the isolation and characterization of a genetic suppressor of the kea1kea2 phenotype.…”
mentioning
confidence: 99%
See 1 more Smart Citation